Change of Temperature of Cotton and Polyester Fabrics in Wetting and Drying Process (Journal of Fiber Bioengineering and Informatics, 2012)
The purpose of this study was to measure temperatures of cotton and polyester woven fabrics in wettingand drying process by thermocouples placed on them. It also discussed temperature distribution causedby diffusion and evaporation at different relative humidity. The measurement points of thermocoupleswere located at two concentric circles with radius of 3 cm and 6 cm. The temperatures were measured bycovering the same fabric when a droplet of water dropped on the center of circle at 20%RH, 65%RH and80%RH environmental moistures, respectively. The results showed that because of diffusion determinedby distance, it was different of temperature changes of every point. As the center of circle, at differenthumidity, temperatures when reached dynamic heat balance were different. The drying process of cottonshowed consistency with temperature recovery. At 20%RH, it is the shortest for temperature returningto environmental temperature because of diffusion speed caused by steam content of environment. Itcan be applied to performance assessment for fabrics that liquid water absorbing function is required. Italso can be used for evaluation of discomfort of wet fabrics by temperature decline with the wetting.